Our roles are not at ease: The work of engaging a youth advisory council in a mental health services delivery organization - Eugenia Canas; Nadine Wathen; Helene Berman; Paula Reaume‐Zimmer; Srividya N. Iyer (Wiley, 2021)
Abstract Objectives There is growing policy impetus for including youth voices in health services research and health system reform. This article examines the perspectives of professionals in a mental healthcare organization charged with engaging young people as advisors in service transformation. Methods An institutional ethnography of a youth mental health services organization in Ontario, Canada, was conducted. Fieldwork consisted of twelve months of observation of meetings, interviews with youth advisors and adult service providers, with subsequent text analysis of engagement training and policy materials. The present article reports data from six adult professionals and related field observations. Results Service providers' efforts to engage youth were observed in three areas: a) supporting youth's development as advisors, b) retaining and deepening youth participation while waiting for organizational change and c) embedding relationships between youth and adults at various levels within the system of care. This work denotes existing tensions between the values and ideals of youth engagement and the everyday demands of services delivery. Conclusion In this setting, a fundamental dimension of this work consisted of negotiating tensions between the policy enthusiasm for engagement and its realization in a health services context. In describing these contextual challenges, we outline implications for consideration by other youth mental health services. Engagement efforts that are authentic and sustained require resources and flexibility, and leadership commitment to instil service users' perspectives throughout multiple levels within the organization.